Corporate governance in a changing economic and political environment : - Federowicz, Michal (Palgrave Macmillan, 2003)
This collection provides exceptional descriptive and analytical insights into changes in corporate governance settings in ten Eastern and Western European countries. It demonstrates that there exist different varieties of capitalism and paths to transformation of economic institutions. In addition, it offers detailed discussions about national cases as well as the overall European Union effects. This book should be of great interest to scholars and students of comparative national systems, corporate governance and European studies.